2008
DOI: 10.1097/nen.0b013e318180ec64
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy Transgenic Mice Exhibit Pathologic Abnormalities in Diaphragm Neuromuscular Junctions and Phrenic Nerves

Abstract: Myotonic dystrophy Type 1 (DM-1) is caused by abnormal expansion of a (CTG) repeat located in the DM protein kinase gene. Respiratory problems have long been recognized to be a major feature of this disorder. Because respiratory failure can be associated with dysfunction of phrenic nerves and diaphragm muscle, we examined the diaphragm and respiratory neural network in transgenic mice carrying the human genomic DM-1 region with expanded repeats of more than 300 CTG, a valid model of the human disease. Morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Moreover, the AChR density on postsynaptic membranes was significantly lower. It should be noted that in previous experiments in DM1 transgenic mice carrying only 500 CTG repeats we detected similar abnormalities in the structure of diaphragmatic EPs (Panaite et al, 2008). The fact that the statistical analysis revealed that the pathological changes in diaphragmatic EPs found in DMSXL mice, carrying about 1300 CTG repeats, do not vary significantly from those observed in DM1 mice indicates that there is no relationship between the severity of EP alterations and length of the CTG repeat.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, the AChR density on postsynaptic membranes was significantly lower. It should be noted that in previous experiments in DM1 transgenic mice carrying only 500 CTG repeats we detected similar abnormalities in the structure of diaphragmatic EPs (Panaite et al, 2008). The fact that the statistical analysis revealed that the pathological changes in diaphragmatic EPs found in DMSXL mice, carrying about 1300 CTG repeats, do not vary significantly from those observed in DM1 mice indicates that there is no relationship between the severity of EP alterations and length of the CTG repeat.…”
Section: Discussionsupporting
confidence: 82%
“…After testing the respiratory function, mice were deeply anesthetized and the brainstem, cervical spinal cord, right and left phrenic nerves and diaphragm muscles carefully removed from each animal as previously described (Panaite et al, 2008; Panaite et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that muscle deficits are not cell autonomous, but depend partly on RNA toxicity in other cells, such as motor neurons. 43, 44 A limitation of our study, however, is that resolution and sizing of large CTG fragments on Southern blots is not precise. Alternative technologies to confirm expansion size are needed but are not currently available.…”
Section: Discussionmentioning
confidence: 95%